2019
DOI: 10.1111/jam.14294
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of maltocin S16, a phage tail‐like bacteriocin with antibacterial activity againstStenotrophomonas maltophiliaandEscherichia coli

Abstract: Aims To determine the characteristics of the novel phage tail‐like bacteriocin (PTLB) produced by Stenotrophomonas maltophilia S16. Methods and Results A screen to identify novel bacteriocins from a panel of 86 S. maltophilia strains was performed. We found that 62 tested S. maltophilia strains were sensitive to a PTLB, designated maltocin S16. In addition, 8 of 14 tested Escherichia coli strains were also susceptible to maltocin S16. Minimum inhibitory concentration determination confirmed that maltocin S16 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Similar results were found in various other reports where bacteriocin was inactivated when treated with proteolytic enzymes (J. Chen et al, 2019;Le et al, 2019).…”
Section: Effect Of Ph Temperature and Enzymes On Bacteriocin Stabilitysupporting
confidence: 92%
“…Similar results were found in various other reports where bacteriocin was inactivated when treated with proteolytic enzymes (J. Chen et al, 2019;Le et al, 2019).…”
Section: Effect Of Ph Temperature and Enzymes On Bacteriocin Stabilitysupporting
confidence: 92%
“…R-type phage-tail-like bacteriocins are nonflexible and have tubes surrounded by contractile sheaths [ 25 ]. They initially make a channel in the cell membrane and successively drive their internal core into the cell.…”
Section: Antimicrobial Peptides’ Natural Sourcementioning
confidence: 99%
“…F-type phage-tail-like bacteriocins are flexible and noncontractile [ 25 ]. They act similarly to R-type bacteriocins [ 27 ].…”
Section: Antimicrobial Peptides’ Natural Sourcementioning
confidence: 99%
“…These large protein complexes resemble the tails of Siphoviridae and Myoviridae phage particles and have bactericidal activity against bacteria related to the producing strain [179]. Two PTLBs have been identified in S. maltophilia, maltocin P28 and S16 [171,180]. Liu and colleagues identified maltocin P28 as phage tail-like particles in electron micrographs of filamentous phage ΦSHP2; purification of these particles indicated that they contained no genetic material but had antimicrobial activity against both environmental and clinical S. maltophilia isolates [171].…”
Section: S Maltophilia Phagesmentioning
confidence: 99%
“…Liu and colleagues identified maltocin P28 as phage tail-like particles in electron micrographs of filamentous phage ΦSHP2; purification of these particles indicated that they contained no genetic material but had antimicrobial activity against both environmental and clinical S. maltophilia isolates [171]. In 2019, the same group of researchers published on a second maltocin, S16, that had broad antibacterial activity against 62 out of 86 S. maltophilia strains tested and remarkably eight out of 14 E. coli strains [180]. The authors suggest that maltocins are widespread in S. maltophilia, possibly providing a range of novel antimicrobial alternatives to antibiotics yet to be discovered.…”
Section: S Maltophilia Phagesmentioning
confidence: 99%